NALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN KESEHATAN DI KLINIK PERKEBUNAN SIMPANG GAMBIR LINGGA BAYU KABUPATEN MANDAILING NATAL TAHUN 2020 - nurleni nasution (Jurnal Kajian Kesehatan Masyarakat, 2020)
Analyzing the factors related to the utilization of health services in Simpang Gambir Plantation Clinic, Lingga Bayu District, Mandailing Natal District 2020 This type of research used in this study is an analytic survey with cross-sectional approach. Determination of sample size using the Lemeshow formula so that the number of respondents is determined to be 100 people. The results showed that there was a relationship between perception (p-value = 0.03), distance (p-value = 0.006), information about health services (p-value = 0.01) , Health Services (p-value = 0.005) and Availability of Medicines (p-value = 0.004). Distance variable has a p-value of 0.045 in Multivariate analysis so it can be assumed that Distance variable is the most influential variable. Based on the Exp (B) value, it can be seen that the largest value is the Information variable about Health Services that is 6.313 so it can be assumed that respondents who get information about Health Services at Simpang Gambir Lingga Bayu Plantation Clinic have more opportunities to utilize Health Services in the Clinic as much as 6.313 times greater than those who lack information. It is expected that the Clinical Managerial and Health Officers can form a Marketing Team that will later be tasked with disseminating information about health services at the Simpir Gambir Lingga Bayu Plantation Clinic.